1994
DOI: 10.1177/001872679404701006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Look at Dual Commitment: An International Study

Abstract: North American scholars have had an historical interest in the extent to which workers can be committed to both their employer and their union. This is particularly relevant given the recent emphasis on greater labor-management cooperation as part of a competitive strategy. This paper reviewed the correlational literature concerning the relationship between company and union commitment. Meta-analysis procedures were applied to the results of 76 samples involving a total of 15,699 respondents and found a mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…The accumulated data on this issue led to three meta-analyses on the relationship between the two variables. Reed, Young and McHugh (1994) found a mean corrected correlation of .42, which supported the notion of the existence of dual commitment. Bamberger, Kluger and Suchard (1999) found a corrected correlation of .36 in 41 samples involving a total of 17,935 respondents.…”
Section: Identification Of Dual Commitmentsupporting
confidence: 54%
“…The accumulated data on this issue led to three meta-analyses on the relationship between the two variables. Reed, Young and McHugh (1994) found a mean corrected correlation of .42, which supported the notion of the existence of dual commitment. Bamberger, Kluger and Suchard (1999) found a corrected correlation of .36 in 41 samples involving a total of 17,935 respondents.…”
Section: Identification Of Dual Commitmentsupporting
confidence: 54%
“…It appears that a sense that the administration can be trusted to represent employee needs and concerns reduces the belief that a union is necessary. This is not the case in all organizations, as evidence has shown widely disparate relationships between organizational commitment and union commitment depending on the context (Bamberger et al, 1999;Reed, Young, & McHugh, 1994). However, in our specific research site, there were clearly antagonisms between the union and administration, with the administration actively campaigning for the removal of the union; the very conditions under which union commitment and organizational commitment are inversely related.…”
Section: A Dual Organization Environmentmentioning
confidence: 69%
“…However, in the wider literature, there have been mixed findings on the organizational commitment-and job satisfaction-union commitment relationships (Reed, Young, and McHugh 1994;Fuller and Hester 1998), and Tan and Aryee"s (2002) Singaporean study found no significant direct effect of job satisfaction on union commitment. In light of such mixed findings, we consider moderation effects (see below).…”
Section: Antecedents Of Union Commitmentmentioning
confidence: 92%
“…For example, whilst most studies have shown a positive association between organizational commitment and union commitment (e.g., Magenau, Martin, and Peterson 1988), some show a negative association (Reed, Young, and McHugh 1994;Fuller and Hester 1998), and IR climate has been identified as a possible moderator of this relationship. Again, a cognitive consistency argument applies:…”
Section: The Consequences Of Industrial Relations Climatementioning
confidence: 99%